Allergy to cow's milk proteins and lactase deficiency: a clinical dilemma in infants - A. F. Kiosov (Лечащий Врач)
Background. When allergic to cow's milk proteins and lactase deficiency, the clinical symptoms of the gastrointestinal tract often have great similarities, so neonatologists and pediatricians often have serious difficulties in making a diagnosis. Surveys among professional societies have shown that pediatricians are not sufficiently aware of cow's milk protein allergy and lactase deficiency in infants and need more information on diagnosis and dietary therapy. Clinical difficulties are also related to the fact that with the gastrointestinal form of allergic to cow's milk proteins, secondary lactase deficiency is possible due to immune damage to enterocytes. Due to the difficulties in diagnosing allergic to cow's milk proteins and lactase deficiency, both unnecessary dietary restrictions and insufficient dietary adjustments are recommended.Objective. To provide up-to-date data on clinical manifestations, differential diagnosis and diet therapy in children with allergy to cow's milk proteins and lactase deficiency. This publication will help medical professionals to make a differential diagnosis of allergic to cow's milk proteins and lactase deficiency in children and prescribe proper diet therapy.Conclusion. The choice of therapeutic nutrition in children requires an individual approach. In case of lactase deficiency that is not related to allergic to cow's milk proteins, breastfeeding should not be discontinued in the child and a dairy-free, low- or lactose-free diet should not be prescribed to the mother. Lactose-free and low-lactose milk mixtures, as well as fermented milk mixtures and comfort mixtures containing reduced amounts of lactose, are used in formula-fed infants. With allergic to cow's milk proteins in breastfed infants, products containing cow's milk proteins should be excluded from the mother's diet. Children on artificial feeding are prescribed amino acid and deeply hydrolyzed mixtures. Infants with allergic to cow's milk proteins should not be prescribed lactose-free, low-lactose, fermented milk formulas and comfort mixtures due to the content of cow's milk proteins in the composition. In children with the gastrointestinal form of allergic to cow's milk proteins, dietary therapy is started with deeply hydrolyzed lactose-free mixtures. As intestinal dysfunction is relieved, deeply hydrolyzed lactose-containing mixtures can be gradually introduced into the diet of children with allergic to cow's milk proteins.